A comparative analysis of coherent structures around a pile over rigid-bed and scoured-bottom. (15th April 2021) - Aksel, Murat; Yagci, Oral; Kirca, V.S. Ozgur; Erdog, Eryilmaz; Heidari, Naghmeh
Abstract: Environmentally friendly piled coastal defence structures gained a particular significance in recent years, given these structures do not interrupt the longshore/cross-shore sediment transport. Flow around an emergent pile is known to generate certain typical coherent flow patterns depending on the flow and boundary conditions, as well as geometry. When the bed is erodible, the scouring process, which typically takes place around the pile, significantly alters these generated coherent structures. The primary objective of this study is to understand the influence of the presence of a scour-hole around the pile on the coherent flow structures, time-averaged kinematic characteristics (i.e. mean flow and turbulence) as well as dynamic pressure characteristics. To achieve this objective, a three-dimensional numerical model was utilized. The model that solves the flow around the emergent pile on rigid-bed was calibrated by using a spatially and temporally high-resolution experimental dataset. Later on, high-resolution DEM data of a scoured-bottom from flume experiments were imported into the calibrated model, and the model was run with identical hydraulic conditions with the experiments. Then, the outputs of the two models, with rigid-bed and with scoured-bottom conditions, were comparatively analysed. It was seen that as a consequence of the presence of a scour-hole, lee-wake vortices were dramatically weakened behind the cylinder. Instead of that, a couple of pronounced large-scale counter-rotating streamwise vortices (LSCSV) behind the cylinder dominate the flow domain to a great extent. Results suggest that the presence of a scour-hole on the bed renders the pile more streamlined against the flow. Highlights: The influence of scour-hole on the coherent flow patterns around the pile was investigated using a 3D numerical model. Due to scour-hole, while some coherent flow patterns around the pile are getting weak, some others become more pronounced. This alteration renders the pile more streamlined against the flow.